Tensile and thermal properties of Bambusa arundinacea and Dendrocalamus asper culm fibers - Ardhyananta, H.; Abdul, F.; Widyastuti; Sulistijono; Hassan, A.; Kurniawan, Denni (2014)
Fibers from the culms of Bambusa arundinacea and Dendrocalamus asper were extracted mechanically and chemically treated using alkaline solution. Tensile and thermal properties of both bamboo fibers were examined. Tensile test on the bamboo fibers showed that Bambusa arundinacea fibers have higher strength and stiffness yet lower elongation than Dendrocalamus asper fibers. When the fibers were chemically treated, similar trend on tensile properties was observed but at lower magnitude compared to those shown by untreated fibers. Further characterization revealed that Bambusa arundinacea fibers are of higher fiber diameter and higher cellulose content compared to Dendrocalamus asper fibers. Thermogravimetric analysis showed that both fibers with same treatment have similar thermal stability, with chemically treated fibers are of higher thermal stability than untreated ones. The chemical treatment removed the lignin from the fiber structure, and affected tensile and thermal properties of both bamboos' fibers. © (2014) Trans Tech Publications, Switzerland.